Nanoparticle-mediated defense priming: A review of strategies for enhancing plant resilience against biotic and abiotic stresses - Yadav N.; Bora S.; Devi B.; Upadhyay C.; Singh P. (My University, 2025)
Nanotechnology has emerged as a promising field with the potential to revolutionize agriculture, particularly in enhancing plant defense mechanisms. Nanoparticles (NPs) are instrumental in plant defense priming, where plants are pre-exposed to controlled levels of stress to heighten their alertness and responsiveness to subsequent stressors. This process improves overall plant performance by enabling quicker and more effective responses to secondary stimuli. This review explores the application of NPs as priming agents, utilizing their unique physicochemical properties to bolster plants' innate defense mechanisms. It discusses key findings in NP-based plant defense priming, including various NP types such as metallic, metal oxide, and carbon-based NPs. The review also investigates the intricate mechanisms by which NPs interact with plants, including uptake, translocation, and their effects on plant physiology, morphology, and molecular processes. Additionally, the review examines how NPs can enhance plant responses to a range of stressors, from pathogen attacks and herbivore infestations to environmental stresses. It also discusses NPs' ability to improve plants' tolerance to abiotic stresses like drought, salinity, and heavy metals. Safety and regulatory aspects of NP use in agriculture are thoroughly addressed, emphasizing responsible and ethical deployment for environmental and human health safety. By harnessing the potential of NPs, this approach shows promise in reducing crop losses, increasing yields, and enhancing global food security while minimizing the environmental impact of traditional agricultural practices. The review concludes by emphasizing the importance of ongoing research to optimize NP formulations, dosages, and delivery methods for practical application in diverse agricultural settings. © 2024 Elsevier Masson SAS